El arte mestizo de la Nueva España - Velarde Cruz, Sofía Irene (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
This thesis proposes Mestizo's category to characterize a part important of the artistic works of visual character pint, sculpture and reliefs in architectural diverse groups - that were carried out in the viceroyalty of the New Spain throughout the three centuries of the Spanish domain in Mexico but fundamentally during the XVI century, since in these works one can observe the conjunction of symbolic and aesthetic important elements of the culture Spanish and the culture of the indigenous diverse towns of old Mexico, that which it propitiated the appearance of an art that we can denominate mestizo and of the one that you/they can to come off substantial explanations on the conformation of the culture novohispana and that they allow to understand each other from the aesthetic perspective a part of the Mexican current culture. We should indicate that the time novohispana is one of the more stages important in the history of Mexico since was in this period where we find the conformation of the Mexican culture, constituted by the coalition racial and cultural of the ethnic diverse groups .entre those that those stand out Spaniards, indigenous and black - that populated the territory during the three centuries of the one I dominate Spanish and whose coexistence provoked the cultural diversity that at the moment it can be observed in this country in practically all their manifestations: customs, language, myths, symbols, religion and beliefs.

Esta tesis propone la categoría de Mestizo para caracterizar una parte importante de las obras artísticas de carácter visual –pintura, escultura y relieves en diversos conjuntos arquitectónicos- que se realizaron en el virreinato de la Nueva España a lo largo de los tres siglos del dominio español en México pero fundamentalmente durante el siglo XVI, ya que en estas obras se puede observar la conjunción de importantes elementos simbólicos y estéticos de la cultura española y la cultura de los diversos pueblos indígenas del México antiguo, lo cual propició la aparición de un arte que podemos denominar mestizo y del que pueden desprenderse substanciales explicaciones sobre la conformación de la cultura novohispana y que nos permiten entender desde la perspectiva estética una parte de la cultura mexicana actual. Debemos indicar que la época novohispana es una de las etapas más importantes en la historia de México ya que fue en este período donde encontramos la conformación de la cultura mexicana, constituida por la fusión racial y cultural de los diversos grupos étnicos –entre los que sobresalen los españoles, indígenas y negros- que poblaron el territorio durante los tres siglos del domino español y cuya convivencia provocó la diversidad cultural que actualmente puede observarse en este país en prácticamente todas sus manifestaciones: costumbres, lenguaje, mitos, símbolos, religión y creencias.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2008-0015; Europa; Indígena; Mesoamérica; Mestizo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/47